Identification of a compound heterozygous inactivating ABCC8 gene mutation responsible for young‐onset diabetes with exome sequencing. Issue 2 (19th September 2019) - Matsutani, Norihiko; Furuta, Hiroto; Matsuno, Shohei; Oku, Yoshimasa; Morita, Shuhei; Uraki, Shinsuke; Doi, Asako; Furuta, Machi; Iwakura, Hiroshi; Ariyasu, Hiroyuki; Nishi, Masahiro; Akamizu, Takashi
Abstract: Activating mutations in the ABCC8 gene cause diabetes and inactivating mutations usually cause hyperinsulinemic hypoglycemia in infancy. Patients with hypoglycemia in infancy due to a heterozygous inactivating mutation have been reported to occasionally progress to diabetes later in life. We explored the gene responsible for diabetes in two brothers, who were suspected to have diabetes at 15 and 18 years‐of‐age, respectively, with whole exome sequencing, and identified a compound heterozygous ABCC8 gene mutation (p.Arg168Cys and p.Arg1421Cys). Although their father and mother were heterozygous carriers of the p.Arg168Cys and the p.Arg1421Cys mutation, respectively, neither parent had diabetes. These mutations have been reported to be responsible for hypoglycemia in infancy and function as an inactivating mutation. Our results suggest that the inactivating ABCC8 gene mutation is also important in the etiology of diabetes. Abstract : Pedigree of a family with young‐onset diabetes due to a compound heterozygous inactivating ABCC8 gene mutation (p.Arg168Cys and p.Arg1421Cys). These mutations had been reported to be responsible for hypoglycemia in infancy and be functional inactivating mutations.